IFN-γ promotes τ phosphorylation without affecting mature tangles - Li, Andrew (FASEB J, 2015)
Inflammatory activation precedes and correlates with accumulating τ lesions in Alzheimer’s disease and tauopathies. However, the relationship between neuroinflammation and etiology of pathologic τ remains elusive. To evaluate whether inflammatory signaling may promote or accelerate neurofibrillary tangle pathology, we explored the effect of recombinant adeno-associated virus (rAAV)-mediated overexpression of a master inflammatory cytokine, IFN-γ, on τ phosphorylation. In initial studies in primary neuroglial cultures, rAAV-mediated expression of IFN-γ did not alter endogenous τ production or paired helical filament τ phosphorylation. Next, we tested the effect of rAAV-mediated expression of IFN-γ in the brains of 2 mouse models of tauopathy: JNPL3 and rTg4510. In both models, IFN-γ increased 1) signal transducer and activator of transcription 1 levels and gliosis, and 2) hyperphosphorylation and conformational alterations of soluble τ compared with control cohorts. However, sarkosyl-insoluble phosphorylated τ levels and ubiquitin staining were unaltered in the IFN-γ cohorts. Notably, IFN-γ–induced τ hyperphosphorylation was associated with release of the inhibitory effect of glycogen synthase kinase 3β function by decreasing Ser9 phosphorylation. Our data suggest that type II IFN signaling can promote τ phosphorylation by modulating cellular kinase activity, though this is insufficient in accelerating neuritic tangle pathology.—Li, A., Ceballos-Diaz, C., DiNunno, N., Levites, Y., Cruz, P. E., Lewis, J., Golde, T. E., Chakrabarty, P. IFN-γ promotes τ phosphorylation without affecting mature tangles.